Fluorinated pyrazoline-linked axial silicon phthalocyanine, alpha (?) and beta (?) zinc phthalocyanines on photophysicochemical properties - Yalazan, Halise; Omeroglu, Ipek; celik, Gonca; Kantekin, Halit; Durmuş, Mahmut (Elsevier Science Sa, 2023)
This study is focused on the photophysical and photochemical properties of silicon and zinc phthalocyanines. Fluorinated pyrazoline-linked axial silicon phthalocyanine (HY-SiPc), peripheral zinc phthalocyanine (HY-ZnPc beta), and non-peripheral zinc phthalocyanine (HY-ZnPc alpha) were synthesized and their structural character-izations were carried out by known Mass, NMR, UV-Vis, and FT-IR techniques. The concentration (in DMSO) and solvent effects (THF, DMSO, CHCl3, DMF, and EtOAc) of the phthalocyanine compounds were studied. The ef-fects of the metal ion in the ring cavity (Zn2+ or Si4+) and the binding positions of the substituted group on photodynamic therapy properties were comparatively investigated. The photochemical and photophysical measurements were investigated in dimethylsulfoxide (DMSO). Examining the results, fluorinated pyrazoline-linked axial silicon phthalocyanine (HY-SiPc) showed the highest singlet oxygen production in this solvent and can be candidate a photosensitizer for PDT.
Keywords: Phthalocyanine; Photodynamic therapy; Photosensitizer; Pyrazoline; Singlet oxygen